PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Virginia Virginia; Kirmizi Kirmizi; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine the influence of firm characteristics and corporate governance on tax avoidance. Tax avoidance is a dependent variable in this study that measured by cash effective tax rate. Independent variable in this study are firm characteristics that proxy by leverage, firm size, and fix asset intensity. While corporate governance is proxy by institutional ownership and independent commissioner.The sample of this research are the manufacture firms listed in Indonesian Stock Exchange in 2012-2014. The sample are collected using purposive sampling method and resulted 53 firms become the samples. Data analyzed by classic assumption tests and examination hypothesis by multiple regression method.The result of this research show that leverage have a significant effect to tax avoidance. While the other variable, firm size, fix asset intensity, institutional ownership, and independent commissioner do not have significant effect to tax avoidance.Keywords : Tax Avoidance, Leverage, Firm Size, Fix Asset Intensity, Institutional Ownership, Independent Commissioner.